Comparison of Gene Expression Between Two Types of Anti-EGFRvIII ScFv Antibodies Having Different Variable Domain Orders in Escherichia coli - Dewi, Kartika Sari; Fuad, Asrul Muhamad (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2017)
Several studies reported that the expression of various kinds of Single-chain variable fragment (scFv) antibodies in Escherichia coli are significantly influenced by the order of their variable domains. To date, the effect of the order of variable domains in the expression of scFv antibodies against epidermal growth factor receptor variant III (EGFRvIII) has not been reported. This study aimed to compare the expression between VH-linker-VL and VL-linker-VH domain orders of the anti-EGFRvIII scFv antibodies in E. coli expression system. Recombinant plasmids inserted with DNA encoding scFv proteins were transformed into E. coli NiCo21(DE3) competent cells and characterized by colony PCR. The expression of scFv proteins was done by using optimum concentration of inducer. Total proteins, soluble periplasmic and cytoplasmic proteins, also extracellular proteins were isolated, subsequently characterized by SDS-PAGE, Slot Blot, and ImageJ software analyses. The antigen-binding activity of both scFvs proteins against EGFRvIII was observed. The results showed that the relative percentage of scFv expression with VH-linker-VL domain order is higher than that of VL-linker-VH in each compartment. Moreover, both of scFvs proteins have antigen-binding activity against EGFRvIII.